Back Cover: Template‐Guided Ionic Self‐Assembled Molecular Materials and Thin Films with Nanoscopic Order (ChemNanoMat 4/2015). Issue 4 (August 2015) - Santella, Marco; Amini, Fatima; Andreasen, Kristian B.; Aswad, Dunya S.; Ausar, Helene; Austin, Lillian Marie; Bora, Ilkay; Boye, Ida M. I.; Brinkenfeldt, Nikolaj K.; Bøe, Magnus F.; Cakmak, Emine; Catovic, Alen; et al.
Abstract : Self‐Assembly . Self‐organizing materials allow for fabrication of functional nanostructures. A two‐component approach to self‐assembled nanostructures has been developed, which allows for simple preparation of thin films with lamellar molecular order. The nanoscale molecular order is maintained over centimeters and is a direct result of the tailored chemical properties of the materials. Furthermore, the two‐component approach allows for different functions to be incorporated in the thin films. For more information, see the Full Paper onpage 253 by Thomas Just Sørensen and co‐workers, which is featured on the back cover. Cover image kindly provided by Merlin von Soosten.